Effects of Alcohol Consumption and Abuse Among Younger Adults in Nsukka, Nigeria - Iwuagwu, Anthony Obinna; Iyiani, Christian Chiedozie; Ngwu, Christopher Ndubuisi; Agholor, Stanley Emeka; Eyang, Brian Obue; Okah, Paulinus Sunday (Advances in Social Sciences Research Journal, 2020)
Globally, there has been availability and misuse of alcohol among youths and the consequences have been a thing of serious concern. This study investigates the effects of alcohol consumption and abuse among younger adults in Nsukka, Nigeria. The study used a multi stage random sample of 110 younger adults aged 17-40 years. They were interviewed using in-depth interviews (10) and Focus Group Discussions (10 FGD) that elicited information on the effects of alcohol consumption and abuse among younger adults. The qualitative data generated were analyzed in themes. Results indicate that majority of the respondents negatively perceived alcohol consumption to be depraved due to its health, religious and social implications, especially when it is abused. However, they conserved that many positive benefits are inherent in alcohol consumption if it is not abused. Given the rate of alcohol abuse among younger adults as findings show, there is the urgent need for policies and programmes that will help regulate alcohol consumption and abuse. This will go a long way in sensitizing, rehabilitating and reintegrating alcohol addicts and the at-risk persons to the larger society and the findings has potentials to influence policies on alcoholism.